Legal and Geopolitical Dynamics in the Delimitation of the Continental Shelf Boundaries among Indonesia, Australia, and Timor-Leste in the Timor Sea - Yanto M.P. Ekon; Alfred G.O Kase; Melkianus Ndaomanu; Tontji Christian Rafael (PT. Global Research Collaboration, 2026)
This study analyzes the legal inconsistency in the delimitation of continental shelf boundaries in the Timor Sea involving Indonesia, Australia, and Timor-Leste. It focuses on the contrast between the Indonesia–Australia Continental Shelf Agreement of 1972, which applies a special circumstances approach based on geological features, and the Australia–Timor-Leste Maritime Boundary Treaty of 2018, which adopts the median line principle in accordance with the United Nations Convention on the Law of the Sea (UNCLOS) 1982. This research employs a normative legal method, examining international treaties, legal doctrines, and relevant judicial decisions. The findings indicate that the difference in delimitation methods results from both the absence of trilateral negotiations and the evolution of international maritime law. The application of geological considerations in the 1972 agreement has led to a delimitation outcome that significantly disadvantages Indonesia, while the 2018 treaty reflects a more equitable and modern legal approach. This inconsistency creates legal uncertainty and raises concerns regarding fairness in the allocation of continental shelf areas. The study further demonstrates that Indonesia has strong legal grounds to seek renegotiation or adjustment of the 1972 agreement, particularly in light of the principles of equity and distance-based criteria under UNCLOS 1982. A consistent application of these principles is essential to ensure fairness and legal certainty in maritime boundary delimitation.